Pengaruh Arus Kas, Profitabilitas dan Ukuran Perusahaan Terhadap Financial Distress (Studi Kasus Pada Perusahaan Real Estate Yang Terdaftar di Bursa Efek Indonesia Periode 2018 – 2020) - Suci Apriyani; Solihin Sidik; Rina Maria Hendriyani (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
This study aims to determine the effect of cash flow, profitability, and firm size on Financial Distress. The research method used is a quantitative descriptive and verification approach. The sample taken consisted of 45 Real Estate companies with annual financial statements.Based on the analysis of research data, the following conclusions are obtained: (1) cash flow has no effect on financial distress (2) Profitability has a positive and significant effect on financial distress (3) Company size has a negative and significant effect on financial distress.